2023
DOI: 10.1155/2023/2944871
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Acoustic Emission Characteristics of Granite and Sandstone under Uniaxial Compression

Abstract: In order to better apply acoustic emission technology to engineering practice, this paper carried out indoor acoustic emission test, and uniaxial compression tests of granite and sandstone under monotonic loading and grading loading were carried out and monitored. The influencing factors of the acoustic emission characteristics of the two rock samples were discussed and the characteristics of the acoustic emission signals corresponding to different stages of rock failure were analyzed. The analysis of the test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Due to the heterogeneity of rock materials, not all external work is converted into elastic strain energy and stored inside the material, and it is accompanied by other forms of energy dissipation, such as elastic strain energy[28], acoustic emission [29][30][31] that releases energy in the form of elastic waves phenomenon: deformation energy [32], which causes the internal state of the material to change, thermal energy [33], and so on. This portion of the energy is primarily used to reconstruct the internal stress eld distribution, as well as to generate and decimate micro-cracks, which have been observed by the acoustic emission study of rock specimens under uniaxial loading [23, 26, 29-32, 34, 35].…”
Section: Energy Conversion Analysismentioning
confidence: 99%
“…Due to the heterogeneity of rock materials, not all external work is converted into elastic strain energy and stored inside the material, and it is accompanied by other forms of energy dissipation, such as elastic strain energy[28], acoustic emission [29][30][31] that releases energy in the form of elastic waves phenomenon: deformation energy [32], which causes the internal state of the material to change, thermal energy [33], and so on. This portion of the energy is primarily used to reconstruct the internal stress eld distribution, as well as to generate and decimate micro-cracks, which have been observed by the acoustic emission study of rock specimens under uniaxial loading [23, 26, 29-32, 34, 35].…”
Section: Energy Conversion Analysismentioning
confidence: 99%
“…As a dynamic and nondestructive evaluation method, acoustic emission (AE) technology can directly reflect the damage inside the material from deformation to failure [24], which has been widely used in the fields of geotechnical engineering, seismic monitoring and rock failure prediction [25][26][27][28]. Mao and Towhata [29] used AE detection to monitor the single-particle fragmentation process under static action, found that the AE characteristics of particle fragmentation process were significant, at first the AE signal activity was relatively low, then entered the inactive period, finally, it was significantly active again and exhibited high-frequency AE signal aggregation prior to impending fracture failure, which provided important information for elucidating the initiation and propagation of internal cracks during particle crushing.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35][36][37] AE signals can be used to determine the evolution process of internal cracks in rocks and thus capture the precursor information of rock instability and failure. Scholars used AE characteristic parameters to study the characteristics and processes of rock rupture, such as AE count, [38][39][40] AE amplitude, 41,42 AE frequency, 43,44 and AE energy. 11,12 In this paper, AE technology was employed to monitor uniaxial compression and creep experimental process of high-temperature heat treated sandstone in real time.…”
Section: Introductionmentioning
confidence: 99%